Prevalence of chronic liver disease and cirrhosis by underlying cause in understudied ethnic groups: The multiethnic cohort. Issue 6 (17th July 2016) - Setiawan, Veronica Wendy; Stram, Daniel O.; Porcel, Jacqueline; Lu, Shelly C.; Le Marchand, Loïc; Noureddin, Mazen
Abstract : Chronic liver disease (CLD) and cirrhosis are major sources of morbidity and mortality in the United States. Little is known about the epidemiology of these two diseases in ethnic minority populations in the United States. We examined the prevalence of CLD and cirrhosis by underlying etiologies among African Americans, Native Hawaiians, Japanese Americans, Latinos, and whites in the Multiethnic Cohort. CLD and cirrhosis cases were identified using Medicare claims between 1999 and 2012 among the fee‐for‐service participants (n = 106, 458). We used International Classification of Diseases Ninth Revision codes, body mass index, history of diabetes mellitus, and alcohol consumption from questionnaires to identify underlying etiologies. A total of 5, 783 CLD (3, 575 CLD without cirrhosis and 2, 208 cirrhosis) cases were identified. The prevalence of CLD ranged from 3.9% in African Americans and Native Hawaiians to 4.1% in whites, 6.7% in Latinos, and 6.9% in Japanese. Nonalcoholic fatty liver disease (NAFLD) was the most common cause of CLD in all ethnic groups combined (52%), followed by alcoholic liver disease (21%). NAFLD was the most common cause of cirrhosis in the entire cohort. By ethnicity, NAFLD was the most common cause of cirrhosis in Japanese Americans, Native Hawaiians, and Latinos, accounting for 32% of cases. Alcoholic liver disease was the most common cause of cirrhosis in whites (38.2%), while hepatitis C virus was the most common cause in African Americans (29.8%). Conclusions: We showed racial/ethnic variations in the prevalence of CLD and cirrhosis by underlying etiology; NAFLD was the most common cause of CLD and cirrhosis in the entire cohort, and the high prevalence of NAFLD among Japanese Americans and Native Hawaiians is a novel finding, warranting further studies to elucidate the causes. (Hepatology 2016;64:1969‐1977)